Exploração sexual comercial de adolescentes: apreendendo o fenômeno a partir de diferentes narrativas - Silva, Rogério Araújo da (2014)
In this thesis, we are going to show a research made with the commercial sexual exploration of teenagers in Goiânia town and nearby it in the period of 2011 to 2013. The main objective is to understand the new configurations of commercial sexual exploration of teenagers nowadays. For that, we start of the principle that, in the last years, the phenomenon got new configurations, closely in the fact that refers to its notorious fact. The importance of this study is justified by the few researches realized about the theme in national, according to the few studies realized up to this time. In the context of a historical process, we will realize a return of how a concept of commercial sexual exploration of children and teenagers was made or remake in Brazil in the last decades. So, we are defining and distinguing some diferente cathegories of the own concept as exploration, violence, power, injury, sexual work, sexual market, prostitution and anothers. The caracterization of the phenomenon is made by the narratives of the people researched, as well as the teenagers and the envolved actors in the universe as the profissionals that do the question. To contextualize the phenomenon in extent worldwide and national, it is delineation a outlook in base in data collected por some organizations. We also approach the legal goal and the national legislation refers to affront of this problem in Brazil. The methodological course and the implications of work in locus are described and debated. The demation of construction of teenagers’ identities in their many dimentions are comprehended. At least, the diferente modalities of commercial sexual exploration of teenagers are made in the sense to understand their new dinamics and configurations.